A non-synonymous coding change in the CYP19A1 gene Arg264Cys (rs700519) does not affect circulating estradiol, bone structure or fracture - Wang, J.; Deogan, M.; Lewis, J.; Chew, S.; Mullin, B.; McNab, Tegan; Wilson, S.; Ingley, E.; Prince, R. (BioMed Central Ltd., 2011)
Background: The biosynthesis of estrogens from androgens is catalyzed by aromatase P450 enzyme, coded by the CYP19A1 gene on chromosome 15q21.2. Genetic variation within the CYP19A1 gene sequence has been shown to alter the function of the enzyme. The aim of this study is to investigate whether a non-synonymous Arg264Cys (rs700519) single nucleotide polymorphism (SNP) is associated with altered levels of circulating estradiol, areal bone mineral density or fracture.Methods: This population- based study of 1,022 elderly Caucasian women (mean age 74.95 ± 2.60 years) was genotyped for the rs700519 SNP were analyzed to detect any association with endocrine and bone phenotypes.Results: The genotype frequencies were 997 wildtype (97.6%), 24 heterozygous (2.3%) and 1 homozygous (0.1%). When individuals were grouped by genotype, there was no association between the polymorphism and serum estradiol (wildtype 27.5 ± 16.0; variants 31.2 ± 18.4, P = 0.27). There was also no association seen on hip bone mineral density (wildtype 0.81 ± 0.12; 0.84 ± 0.14 for variants, P = 0.48) or femoral neck bone mineral density (0.69 ± 0.10 for wildtype; 0.70 ± 0.12 for variants, P = 0.54) before or after correction of the data with age, height, weight and calcium therapy. There were also no associations with quantitative ultrasound measures of bone structure (broadband ultrasound attenuation, speed of sound and average stiffness).Conclusions: In a cohort of 1,022 elderly Western Australian women, the presence of Arg264Cys (rs700519) polymorphism was not found to be associated with serum estradiol, bone structure or phenotypes. © 2011 Wang et al; licensee BioMed Central Ltd.